The results of research should be open to all - Markov, Alexander (Морфологія / Morphologia / Morfologìâ, 2010)
The old system of financing scholarly publications, in which the main burden of costs falls on the reader, impedes the development of science and society and does not correspond to the realities of today, when the cost of spreading information through the Internet is virtually close to zero. The Plos Biology magazine has published an editorial on open access issues. However, while in the West thousands of highly rated scientific journals are already operating in open access mode, virtually all leading Russian academic journals are still not available to a wide reader due to excessively high subscription and retail prices.